ETIKA KOMUNIKASI PERSPEKTIF AL-QUR’AN: TELAAH KRITIS SOLUSI MENGATASI PROBLEMATIKA HOAX DI MEDIA SOSIAL - muhamad irhamdi (AL-IDZA'AH: Jurnal Dakwah dan Komunikasi, 2022)
Abstract. The insistence of the flow of social media must be acknowledged that it brings various consequences in the line of life that must be borne by modern civilization. In addition to offering as an enjoyment of life that tends to be material and physical, social media has brought many negative impacts, especially in the social area. Good communication ethics over time and changing times have eroded. The number of hoax news that is scattered in the media seems to be human food for social media users. The contextualization of the holy book (al-Qur'an) today is the right answer to this modern problem. the main focus in this research is tracking the deep communication ethics of the Qur'an as a solution in responding to the problem of hoaxes on social media. The type of research used is library research, namely research that is used to solve conceptual-theoretical problems. The data sources used in this paper are primary and secondary sources. The analytical method of writing this work is descriptive-analytical. Keywords: Al-Qur'an, Problematics, Social Media